STABILIZED ERRORS: ATTRIBUTED PROBLEM IN TIMED AND NON-TIMED ARGUMENTATIVE WRITING - Nur Indah, Rohmani (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2014)
This study is a case study seeking the relation between the errors students made in timed and non-timed argumentative writing. The use of good English language influences whether or not the students can develop their claim. The finding shows that students have fifteen types of stabilized errors, the dominant of which are verb tense, word choice and spelling. On language form, the stabilized errors mostly occur are omission and addition. Some students also show stabilized errors with reference to the negative transfer of their first language. In addition, the type of writing task results in different number of stabilized errors. Despite the favor on non-timed writing, some students show more careful language use without using the computer’s spelling and grammar check. However, the type of writing task does not affect the number of errors as there is no significant difference between the two writing tasks. It supports the fact that post systematic errors are caused by several factors such as language transfer, intralingual interference and sociolinguistic situation. Accordingly, process approach writing is needed in which learners are given chance to make progress and, as suggested by Krashen’s theory, to become optimal Monitor users.